SISTEM INFORMASI PENDATAAN PENDUDUK TERPADU PADA KANTOR KECAMATAN KOTA PALEMBANG - Megawaty _ (IST AKPRIND Yogyakarta, 2018)
Utilization of information technology today is felt very helpful for various activities and human needs. One of the benefits is the job becomes more effective and efficient, simplify, and speed up a job. But behind the ease can not be felt optimally by the administration of the sub-district kemuning Palembang city, this is caused by the data management of the population who received help from poor rice in the city of palembang kemuning not system properly, data collection has been done by doing manual recording on the ledger , large document storage, data search process also requires time because the data sought is documented in physical form. Therefore, the authors feel the need to do this research by building a system that specifically manages the data of the people who receive rice assistance raskin. The research method used in this research is descriptive and for software development using SDLC (System Development Live Cycle) as for the stages are: planning, analysis, designing, coding, testing, deployment. The benefit of this research is as a container for data storage of the population and the residents who receive assistance, facilitate the process of data collection because it can be input directly into the system, data search effectively when data is needed at any time, data can be stored well in the database system many.